Model yeast as a versatile tool to examine the antioxidant and anti-ageing potential of flavonoids, extracted from medicinal plants - Zahoor, Hira; Watchaputi, Kwanrutai; Hata, Janejira; Pabuprapap, Wachirachai; Suksamrarn, Apichart; Chua, Lee Suan; Soontorngun, Nitnipa (Frontiers in Pharmacology, 2022)
The demand for the production of herbal extracts for cosmetics, food, and health supplements, known as plant-based medicine, is rising globally. Incorporating herbal extracts could help to create higher value products due to the functional properties of bioactive compounds. Because the phytochemical composition could vary depending on the processing methods, a simple bioassay of herbal bioactive compounds is an important screening method for the purposes of functional characterization and quality assurance. As a simplified eukaryotic model, yeast serves as a versatile tool to examine functional property of bioactive compounds and to gain better understanding of fundamental cellular processes, because they share similarities with the processes in humans. In fact, aging is a well-conserved phenomenon between yeast and humans, making yeast a powerful genetic tool to examine functional properties of key compounds obtained from plant extracts. This study aimed to apply a well-established model yeast, Saccharomyces cerevisiae, to examine the antioxidant and anti-aging potential of flavonoids, extracted from medicinal plants, and to gain insight into yeast cell adaptation to oxidative stress. Some natural quercetin analogs, including morin, kaempferol, aromadendrin, and steppogenin, protected yeast cells against oxidative stress induced by acetic acid, as shown by decreased cell sensitivity. There was also a reduction in intracellular reactive oxygen species following acetic acid treatment. Using the chronological aging assay, quercetin, morin, and steppogenin could extend the lifespan of wild-type S. cerevisiae by 15%-25%. Consistent with the fact that oxidative stress is a key factor to aging, acetic acid resistance was associated with increased gene expression of TOR1, which encodes a key growth signaling kinase, and MSN2 and MSN4, which encode stress-responsive transcription factors. The addition of the antioxidant morin could counteract this increased expression, suggesting a possible modulatory role in cell signaling and the stress response of yeast. Therefore, yeast represents a versatile model organism and rapid screening tool to discover potentially rejuvenescent molecules with anti-aging and anti-oxidant potential from natural resources and to advance knowledge in the molecular study of stress and aging.